Analysis of pharmaceutical technical staff needs at hospital X in Bandung using the WISN method - Angela Alysia Elaine; Imam Adi Wicaksono (Pharmaciana)
One of the essential and inseparable health services in hospitals is pharmaceutical services. Pharmaceutical services in hospitals are carried out by the Hospital Pharmacy Installation (Instalasi Farmasi Rumah Sakit / IFRS). The implementation of pharmaceutical services in hospitals must be supported by adequate, skilled, and competent human resources so that pharmaceutical service activities can run well and are high quality for patients. The lack of human resources for pharmaceutical services will result in excessive workload and reduced quality of pharmaceutical services. One method widely used to determine the number of staff needs is the Workload Indicators of Staffing Needs (WISN). Analysis of the need for pharmaceutical technical staff at Hospital X in Bandung City was carried out using the WISN method. The data used for the analysis were obtained from interviews, observations, and data collection on pharmaceutical services from the pharmacy installation of the Hospital X. The results of the WISN analysis showed that the need for pharmaceutical technical personnel for central pharmacy installations providing outpatient and inpatient services is 87 people, the total need for the emergency room pharmacy satellite is 6 people, the operating room pharmacy satellite is 6 people, and the pharmacy warehouse is 3 people. From the results of WISN ratio, the number of pharmaceutical technical staff available for the central pharmacy installation, emergency room pharmacy satellite, and operating room pharmacy satellite are still inadequate for the existing workload (WISN ratio < 1). In contrast, for the pharmaceutical warehouse, it is adequate (WISN ratio = 1). Therefore, Hospital X needs to consider adding existing pharmaceutical technical staff to support more optimal pharmaceutical services at the hospital.